Reliability and maintenance : networks and systems - Beichelt, Frank , 1942-; Tittmann, Peter (CRC Press, 2012)
Reliability and Maintenance: Networks and Systems gives an up-to-date presentation of system and network reliability analysis as well as maintenance planning with a focus on applicable models. Balancing theory and practice, it presents state-of-the-art research in key areas of reliability and maintenance theory and includes numerous examples and exercises. Every chapter starts with theoretical foundations and basic models and leads to more sophisticated models and ongoing research. The first part of the book introduces structural reliability theory for binary coherent systems. Within the frame